Job Skills Education Program. Final Technical Report - Florida State Univ., Tallahassee. Center for Educational Technology; Florida State Univ., Tallahassee. Center for Educational Technology; Ford Aerospace Corp., Newport Beach, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This publication provides materials developed by a project designed to transfer a U.S. Army computer-based basic skills curriculum to applications in the vocational skills development of civilian adults. An executive summary of the final report describes the Job Skills Education Program (JSEP), which teaches academic skills that support vocational training. A technical report describes the range of activities in developing JSEP for use in a civilian environment and demonstrating its effectiveness. A lesson-by-lesson description of the curriculum, which addresses 167 skills, is provided. Contents are further divided into separate volumes. Volumes I and II chronicle individual tasks from the project. Volume III provides an overview of the project procedures and outcomes. These volumes describe the military-to-civilian conversion project. Volume IV is the JSEP Implementation Handbook. It describes the JSEP instructor's roles and responsibilities, JSEP lessons, software and hardware for MicroTICCIT--the computer system on which the civilian version of JSEP runs, courseware operations, and evaluation methods. Extensive appendixes provide prescriptions for 20 occupations, civilian job equivalents for military jobs, sample reports from the student management system, and a glossary. Volume V is a detailed report of the project pilot test conducted in White Plains, New York. Volume VI provides information regarding the availability of JSEP and the hardware and personnel training required for implementation. (YLB)
Sponsoring Agency: Office of Vocational and Adult Education (ED), Washington, DC.
Contract Number: VN88003501.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Education; Adult Basic Education; Basic Skills; Computer Assisted Instruction; Computer Managed Instruction; Curriculum Development; Curriculum Guides; Job Skills; Military Training; Occupations; Program Implementation; Vocational Education; Job Skills Education Program; Reports, Research; Guides, Classroom -- Teacher